How-to establish PCST. Two handbooks on science communication - Alessandro Delfanti (JCOM: Journal of Science Communication, 2008)
In 2008 two collections were published: the Handbook of Public Communication of Science and Technology, edited by Massimiano Bucchi and Brian Trench, and Communicating Science in Social Contexts: New models, new practices, edited by Donghong Cheng and five other scholars from China, Canada, Belgium and Australia. These books try to define and draw the boundaries of science communication’s field from both a theoretical and empirical point of view. But do we need to establish it as a distinct research field? For a number of decades, a growing community of scholars and communicators is trying to reply positively to this question, but the need to look outside the disciplinary boundaries, to other academic fields, is still vital.